Report of the International Workshop on Registration of Farmers’ Varieties, 4-7 December 2018, Entebbe, Uganda. - Recha, Tobias; Muwanika, C.; Otieno, G.; Jonge, B. de; Mulumba, W.; Nankya, R. (Bioversity International, 2019)
The report gives a summary of the proceedings of the international workshop on registration of farmers’ varieties held in Entebbe Uganda between 4-7 December 2018. It provides a summary of experiences from several countries such as Bolivia, Ethiopia, Lao People's Democratic Republic, Nepal, Zimbabwe, and the European Union, where the registration of farmers’ varieties is currently on going or being discussed. It offers valuable policy lessons for countries with regard to pertinent questions on registration and maintenance of farmers' varieties.